Perlindungan Hukum Pekerja Migran Indonesia : Tantangan dan Upaya Penegakan Hak Ketenagakerjaan - Sagita Br. Sinambela; Miranti Puspita Sari; Fadlan Alfathan Harahap; Alifsyah Hilman (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Indonesian migrant workers (PMI) play a strategic role in contributing to the nation's foreign exchange, yet they continue to face numerous violations of labor rights, including exploitation, discrimination, and limited access to legal protection. This study aims to examine the legal protection framework for PMIs, identify the key challenges in its implementation, and propose strategic efforts to strengthen labor rights protection.This research uses a qualitative method with a literature review approach, utilizing legal regulations, academic journals, and official institutional reports as primary data sources. The analysis is carried out descriptively and critically to evaluate the regulations, institutional roles, and dynamics of migrant worker protection both domestically and abroad.The findings indicate that the protection of PMIs remains weak due to limited enforcement of Law No. 18 of 2017, inadequate institutional capacity, and low legal literacy among workers. Moreover, coordination among relevant agencies remains suboptimal. This study recommends institutional reform, enhanced legal education for PMIs, and stronger diplomatic efforts to advocate for migrant workers' rights in destination countries.